Responsabilidade fiscal e paradiplomacia financeira: a recenta experiência creditícia do Estado do Ceará - Bessa, Ricardo Wilson de Souza (2012)
In a recent period with significant and increasing participation by subnational governments – mainly in emerging countries composed by federated states – in international economic relations, this article intends to analyze the influence of macroeconomic, fiscal and politic variables policies at raising the necessary funds by Ceará State from international organizations. Ceará’s austere fiscal management and pro-activeness financial paradiplomacy have provided the credibility needed to get external loans from multilateral and bilateral agencies. The average annual amount of this fund raising is R$ 160 million during the period from 1999 to 2008, representing 40% of the total volume. Thus, based on an ad hoc linear multivariate framework, we can evidence the fiscal reform positive impact, besides the negative influence caused by changes of State executive power management. These loans were also influenced positively by the relative offer and mainly by parallel paradiplomacy effort so that an increase in this variable by 1% implies the increase of 0.22% in fund raising.